Fundamentos constitucionais do direito privado: uma teoria da justiça e da dignidade humana - Dresch, Rafael de Freitas Valle (2011)
The thesis presents a hypothesis to overcome the current misunderstanding related to the diversity of private law beddings, defending the viability of reconciliation of commutative justice and distributive justice as a way to understand the basis of the legal institutions of private law. The study evaluates the formalist, social functionalist and economic functionalist theories of the private law and detects an element shared by all of them: the theory of justice. The identified central problem results from the gradual loss of the relation between law and the Aristotelian-Thomist theory of justice, gradually operated from the Modern School of Natural Law. The disconnection between justice and law, despite keeping a sporadic relation with the particular justice, determined the eradication of the essential meaning of the general justice of the jusprivatists analyses. The analyzed hypothesis defends that the rescue of general justice, transformed into social justice in modern days by the new order centered in the equal dignity of the human being, materialized through the guarantee of the individual basic capacities, allows us to understand that private law is characterized by horizontal relations of rights and duties between individuals who are rationally understood in terms of particular justice (commutative and distributive), commanded by social justice of equal dignity and recognition and institutionalized by the Constitution and the civil rights.